ANALISIS KESULITAN PESERTA DIDIK DALAM MENGERJAKAN SOAL PAS 1 IPA DITINJAU DARI ASPEK HOTS KELAS V SDN KEMBANGKUNING - Herry Nugroho Sulistio; Nur Ngazizah; Suyoto (Jurnal Binagogik, 2024)
This research aims to determine the difficulties experienced by students in solving PAS 1 IPA questions in terms of the HOTS aspect of class V SDN Kembangkuning. The type of research used is descriptive qualitative. The subjects of this research were students of SDN Kembangkuning Purworejo class V for the 2022/2023 academic year. The technique for taking subjects in this research was purposive sampling. There are 3 subjects with high, low and medium abilities. Data collection techniques in this research used capability interviews and documentation. The data obtained is validation of students' HOTS ability interviews. Data analysis, namely: data reduction, data display, and conclusion drawing/verification. The results of this research show that, the analysis of students' difficulties in working on PAS 1 IPA questions is seen from the HOTS aspect of class V SDN kembangkuning, namely that S1 subjects are included in the high level of ability and are able to do all the questions correctly and do not experience difficulties in working on HOTS questions. Subject S2 is included in the medium level of ability to do 4 questions correctly and answered the questions incorrectly because he misunderstood the questions. S3 is included in the low level of ability to be able to do 1 question correctly, where in working on the question you have difficulty reading, difficulty understanding, difficulty transformation.